2010
DOI: 10.1126/science.1194218
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Chemical Commodity Feedstocks from Integrated Catalytic Processing of Pyrolysis Oils

Abstract: Fast pyrolysis of lignocellulosic biomass produces a renewable liquid fuel called pyrolysis oil that is the cheapest liquid fuel produced from biomass today. Here we show that pyrolysis oils can be converted into industrial commodity chemical feedstocks using an integrated catalytic approach that combines hydroprocessing with zeolite catalysis. The hydroprocessing increases the intrinsic hydrogen content of the pyrolysis oil, producing polyols and alcohols. The zeolite catalyst then converts these hydrogenated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
685
3
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,015 publications
(701 citation statements)
references
References 32 publications
7
685
3
6
Order By: Relevance
“…67, 68 Most biomass feedstocks have H/C eff ratios lower than 0.5 due to high oxygen contents while petroleum-based feedstocks have a value between 1-2. 69 The Maplewood has a low value, 0.06 due to high oxygen content.…”
Section: Preparation Of Solid Intermediate Productmentioning
confidence: 99%
“…67, 68 Most biomass feedstocks have H/C eff ratios lower than 0.5 due to high oxygen contents while petroleum-based feedstocks have a value between 1-2. 69 The Maplewood has a low value, 0.06 due to high oxygen content.…”
Section: Preparation Of Solid Intermediate Productmentioning
confidence: 99%
“…[3,4] Biomass, derived from non-edible sources of lignocellulose, sugars, and triglycerides offer the only sustainable and low cost solutions to alternative low carbon/carbon neutral transportation fuels. Thermal processing of lignocellulosic biomass to alkanes via pyrolysis and 2 hydrodeoxygenation (HDO) [5,6] or the conversion of plant or algae oil lipids via transesterification [7,8] to biodiesel are the subject of many investigations targeting low cost renewable transportation fuel. [9] While biodiesel production via the transesterification of C14-C20 triglyceride (TAG) components of lipids with C1-C2 alcohols [10][11][12][13] into fatty acid methyl esters (FAMEs) routes offer an energetically economical route to biofuels, [14] , [15] the use of soluble base catalysts results in fuel contamination and accompanying reactors and engine manifold corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the requisite amount of additional alcohol is lowered and the corresponding economy is improved. However, because the complete saturation of bio-oil components is difficult, the hydrogen supply only by a hydrogenation pre-treatment is not enough and will lead to some coke formation (Vispute et al 2010). Hence, secondary hydrogen supply by cocracking is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a further improvement is required. Researchers have found that bio-oil could be stabilized by mild hydrogenation, in which some aldehydes and ketones were converted to aliphatic alcohols (Vispute et al 2010;Zheng et al 2015). Transition metals such as Ni and Cu are often used for bio-oil hydrogenation because they can activate H2 (Mortensen et al 2011), and bifunctional Ni-Cu was found to exhibit high activity in the hydrogenation of bio-oil (Ardiyanti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation